Considerations towards the possibility of the observation of parity nonconservation in highly charged ions in storage rings - Bondarevskaya, Anastasia A.; Chubukov, D. V.; Mistonova, E. A.; Lyashchenko, K. N.; Andreev, O. Yu; Surzhykov, A.; Labzowsky, L. N.; Plunien, G.; Liesen, Heinz-Dieter; Bosch, F.; Stöhlker, Th (Physica scripta, 2018)
The feasibility of an experiment for the observation of parity nonconserving effects using He-like highly charged ions in storage rings is discussed theoretically. The basic idea is the observation of an asymmetry in the emission of the hyperfine quenched transition with respect to the direction of a beam of ions with polarized nuclei. It will be shown, that for such an experiment 151Eu61+ ions with nuclear spin in the excited electronic state with zero total electron angular momentum and polarized nuclei are the best available candidates. The nuclei can be polarized if H-like Eu62+ ions capture an electron from a polarized electron beam which overlays the ion beam on some part of the ring and travels with nearly the same velocity. It is suggested, to monitor steadily the degree of the nuclear polarization by the observation of the selective laser excitation and subsequent decay of the Zeeman sublevels of the excited hyperfine states of the ionic ground state. Estimates for the observation time aiming at an accuracy of PNC measurement of about are given.
Gesehen am 06.04.2020